Study on the effect of calcium hypochlorite and air as mixed oxidant and a synthesized low cost Pd-Ni/C anode electrocatalyst for electrooxidation of glycerol in an air breathing microfluidic fuel cell - Panjiara D.; Pramanik H. (My University, 2025)
In the present work, glycerol-based air breathing microfluidic fuel cell (μFC) is investigated. The noble metal Pd and non-noble metal Ni-based bimetallic synthesized electrocatalyst (Pd-Ni/C) were used for glycerol electrooxidation and commercial Pt/CHSA was used as cathode electrocatalyst. The anolyte is glycerol mixed with KOH electrolyte. The atmospheric air and calcium hypochlorite mixture are used as oxidant in cathode and catholyte, respectively. Acetylene black carbon is used as electrocatalyst support with low metal loading of 20 wt% Pd and Ni at their different weight ratios (Pd/Ni) of 16:4, 10:10, and 4:16 to synthesize bimetallic Pd-Ni/C anode electrocatalysts. The crystal structure of the synthesized electrocatalyst was determined by X-ray diffraction (XRD) analysis. The surface morphology and surface concentration of synthesized electrocatalyst were determined by scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDX), respectively. The particle size of synthesized electrocatalyst was determined by transmission electron microscopy (TEM) analysis. The electrochemical activity of Pd-Ni/C was investigated by cyclic voltammetry analysis. The electrocatalyst Pd-Ni (10:10)/C gives higher electrocatalytic activity for glycerol electrooxidation compared to other ratios of electrocatalyst. A single air breathing μFC is investigated using various key parameters where air alone as oxidant gives open circuit voltage (OCV) of 0.42 V and maximum power density of 1.27 mW/cm2. While using calcium hypochlorite and air as mixed oxidant, the OCV was increased to 0.72 V and maximum power density increased to 3.43 mW/cm2, which are 1.71 and 2.7 times, respectively, more than that of air as oxidant only. © 2021 Canadian Society for Chemical Engineering.